Utusan Malaysia, 26 May 2008 - Meran Abu Bakar (The Utusan Group, 2008)
A former English teacher, Zainon Mohd. Noor Al-Greece, was not upset at all and felt sorry when she decided to give some of her jewelery to the Terengganu State Museum Board.